Loss of all three APP family members during development impairs synaptic function and plasticity, disrupts learning, and causes an autism-like phenotype - Steubler, Vicky; Erdinger, Susanne; Back, Michaela K; Ludewig, Susann; Fäßler, Dominique; Richter, Max; Han, Kang; Slomianka, Lutz; Amrein, Irmgard; Engelhardt, Jakob von; Wolfer, David Paul; Korte, Martin; et al. (The EMBO journal, 2021)
The key role of APP for Alzheimer pathogenesis is well established. However, perinatal lethality of germline knockout mice lacking the entire APP family has so far precluded the analysis of its physiological functions for the developing and adult brain. Here, we generated conditional APP/APLP1/APLP2 triple KO (cTKO) mice lacking the APP family in excitatory forebrain neurons from embryonic day 11.5 onwards. NexCre cTKO mice showed altered brain morphology with agenesis of the corpus callosum and disrupted hippocampal lamination. Further, NexCre cTKOs revealed reduced basal synaptic transmission and drastically reduced long-term potentiation that was associated with reduced dendritic length and reduced spine density of pyramidal cells. With regard to behavior, lack of the APP family leads not only to severe impairments in a panel of tests for learning and memory, but also to an autism-like phenotype including repetitive rearing and climbing, impaired social communication, and deficits in social interaction. Together, our study identifies essential functions of the APP family during development, for normal hippocampal function and circuits important for learning and social behavior.